To find the first three terms of the arithmetic sequence given the recursive formula, we start with the provided values:
-
First Term:
\( a_1 = -5 \) -
Second Term:
Using the recursive formula \( a_n = a_{n-1} + 4 \): \[ a_2 = a_1 + 4 = -5 + 4 = -1 \] -
Third Term:
Again using the recursive formula: \[ a_3 = a_2 + 4 = -1 + 4 = 3 \]
Putting this all together:
- \( a_1 = -5 \)
- \( a_2 = -1 \)
- \( a_3 = 3 \)
Thus, the first three terms of the sequence are:
- \( a_1 = -5 \)
- \( a_2 = -1 \)
- \( a_3 = 3 \)